A gestão democrática da educação em Alagoas: metamorfoses no campo da cultura organizacional - Gomes, Claudia Campos Cavalcante (2013)
This research conducted a comparative analysis on the organizational culture of two schools in the 13th CRE experiencing the process of democratic management implemented within the public school system in the State of Alagoas state . The initial approach was made with the aim of characterizing the specificities of school administration from the perspective of democratic management , bringing discussions on the School Board and Educational Policy Project , dialogued up , even in the context of this work , with the start of training policy State of Alagoas , was emphasized the centralization of power that has always been present and , nevertheless, the process of implementation of democratic management in schools in state schools from 1999 to 2010 , understood as the study time frame . The study was based on the principles of participative research that combines social investigation , educational work and action based on the process of knowing the object and then the researcher launch proposals and come to act on it. The theoretical framework that has supported the research was based on authors argue that democratic management education and organizational processes such as : Cury , ( 2000), Felix (1989 ) ; Gadotti and Romao ( 2004), Time , (1994 ) ; Libâneo , (2004 ) , (2007 ), Oliveira (1997 ), Paro (2002 ) ; Prado and Diogenes (2011 ) . The results showed that within the schools analyzed , belonging to the 13th CRE in the State of Alagoas , there is a distancing of what is meant by democratic management , since there is no sharing of power , and therefore managers who still direct the planning the work to be performed , not solving the problems of dialogue form with all segments of the school community . In general , the term democratic management of public schools in Alagoas is only limited to documents that circulate in schools since the organizational culture of the same has ensured that there is decentralization and dialogue , so this concept is embedded in the speech delivered by government authorities , but in practice the state of insecurity felt by schools in the state schools the democratization process is yet to be built . Thus , it was found that the sharing of power, essential to the realization of democratic management in the state still represents something to be conquered .